Estimating effective conductivity of unidirectional transversely isotropic composites - Kien, Nguyen Trung; Luat, Nguyen Van; Chinh, Pham Duc (Vietnam Journal of Mechanics, 2013)
Three-point correlation bounds are constructed on effective conductivity of unidirectional composites, which are isotropic in the transverse plane. The bounds contain, in addition to the properties and volume proportions of the component materials, three-point correlation parameters describing the micro-geometry of a composite, and are tighter those obtained in [1]. The bounds, applied to some disordered and periodic composites, keep inside the numerical homogenization results obtained by Fast Fourier method.